ANALISIS PENGARUH PERSEPSI HARGA, SERVICESCAPE, DAN GAYA HIDUP TERHADAP KEPUTUSAN PEMBELIAN PADA COFFEE SHOP DI KOTA SEMARANG - Astridea Artika Arsa; Cahyaningratri Cahyaningratri (Diponegoro Journal of Management, 2022)
In this modern era, coffee shops are growing rapidly. The emergence of this coffee shop has an impact on the consumptive behavior of young adults. Purchasing coffee in several coffee shops is of course influenced by several factors including in terms of price perception, servicescape and lifestyle. Therefore, this research was conducted to determine the effect of price, servicescape and consumer lifestyle on consumer purchasing decisions. This study uses a quantitative method. This research was conducted in Semarang with a population of buyers or consumers who have made a purchase at a coffee shop in Semarang City, the number of which is unknown. While the number of samples that will be used in this study is 30 people per outlet. The data was obtained through the distribution of questionnaires, then the data were analyzed descriptively. The results showed that the perception of price, servicescape, and lifestyle proved to have a positive and significant effect on purchasing decisions, as evidenced by the results of the t-test of price perceptions of 2,602 and sig. 0.011 < 0.05, servicescape t-test of 2.349 and sig. 0.021 < 0.005, and lifestyle t-test of 5.174 and sig. 0.000 < 0.005.